Effectiveness of Bradyrhizobium inoculation at pre-sowing of soybean - Zilli, Jerri Édson; Campo, Rubens José; Hungria, Mariangela (Pesquisa Agropecuaria Brasileira, 2011)
The objective of this work was to evaluate the effect of Bradyrhizobium inoculation on soybean pre-sowing and the effect of the treatments of seeds using fungicides on nodulation. Control treatments consisted of two non-inoculated treatments, with or without N-fertilizer supply (200 kg ha-1 of N). Inoculation at pre-sowing had a performance similar to the standard inoculation at sowing regarding soybean nodulation, dry matter production, grain yield and N accumulation in tissues and grains. However, when seeds were treated with fungicides, nodulation and grain yield decreased.